Land Subsidence Susceptibility Projection for Palembang Slum Area by Complex MCDM-AHP Technique - Deros S.N.M.; Din N.M.; Norzeli S.M.; Omar R.C.; Usman F.; Hamim S.A. (Institute for Research and Community Services, Institut Teknologi Bandung, 2023)
Decision making; Groundwater; Hierarchical systems; Population distribution; Population dynamics; Population statistics; Soil moisture; Subsidence; Analytical Hierarchy Process; Land subsidence; Multi criteria decision-making; Multi-criteria decision making; Multicriteria decision-making; Multicriterion decision makings; Population densities; Slum; Susceptibility maps; Land use